2020
DOI: 10.3390/cli8020028
|View full text |Cite
|
Sign up to set email alerts
|

Future Scenarios of Soil Erosion in the Alps under Climate Change and Land Cover Transformations Simulated with Automatic Machine Learning

Abstract: Erosion is one of the major threats listed in the Soil Thematic Strategy of the European Commission and the Alps are one of the most vulnerable ecosystems, with one of the highest erosion rates of the whole European Union. This is the first study investigating the future scenarios of soil erosion in Val Camonica and Lake Iseo, which is one of the largest valleys of the central Italian Alps, considering both climate change and land cover transformations. Simulations were done with the Dynamic Revised Universal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Such variability might be related to ongoing climate change, with drier summers and wet winters, with limited snowfall, potentially affecting erosion processes. However, the final effects of climate change on soil erosion rates in the Alps are still highly debated, as reported by Gianinetto et al [24], because of the complexity of the factors involved. The importance of summer storms in soil erosion was evident from the data in Table 2 and by the peak erosion intensities computed by the meteorological station.…”
Section: Rainfall Data Soil Erodibility and Erosion Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such variability might be related to ongoing climate change, with drier summers and wet winters, with limited snowfall, potentially affecting erosion processes. However, the final effects of climate change on soil erosion rates in the Alps are still highly debated, as reported by Gianinetto et al [24], because of the complexity of the factors involved. The importance of summer storms in soil erosion was evident from the data in Table 2 and by the peak erosion intensities computed by the meteorological station.…”
Section: Rainfall Data Soil Erodibility and Erosion Estimatesmentioning
confidence: 99%
“…Across the duration of our experiment, no extreme meteorological event was observed, but they were documented in the near past (e.g., a severe erosion after a summer storm occurred in the experimental vineyard in 2012). Additionally, existing literature (e.g., [24,30]) underlined that climate change could worsen erosion processes due to the increase of extreme events, threatening soil conservation. FinallyProsdocimi et al [31] reviewed erosion in Mediterranean vineyards and reported 2.4 t ha −1 rates for erosion plots (single event), but they observed that the maximum rainfall intensity explained only in part the sediment loss.…”
Section: Erosive Events Erosion Measurementsmentioning
confidence: 99%
“…The distribution of rainfall in several areas of the same country or continent can either increase or decrease in the future climate [12]; this is consistent with the prediction of IPCC [61] for the global precipitation changes. Other authors [73][74][75] analyzed the longterm impact of climate change on soil erosion by water and sediment yield, evaluating future climate impact to 2100. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that its occurrence is affected by anthropogenic activities (e.g., urban expansion, infrastructure development, removal of vegetative coverage and uncontrolled land cultivation), natural driving forces, such as the water and wind, are considered as the main triggers. Among them, water is considered the most important [2]. Soil erosion by water is a gravity-driven process wherein the rainfall and/or surface water initially causes the detachment of soil particles (soil loss).…”
Section: Introductionmentioning
confidence: 99%